First Report of a Peroxiredoxin Homologue in Jellyfish: Molecular Cloning, Expression and Functional Characterization of CcPrx4 from Cyanea capillata - Ruan, Zengliang (MDPI, 2014)
We first identified and characterized a novel peroxiredoxin (Prx), designated as CcPrx4, from the cDNA library of the tentacle of the jellyfish Cyanea capillata. The full-length cDNA sequence of CcPrx4 consisted of 884 nucleotides with an open reading frame encoding a mature protein of 247 amino acids. It showed a significant homology to peroxiredoxin 4 (Prx4) with the highly conserved F-motif ((93)FTFVCPTEI(101)), hydrophobic region ((217)VCPAGW(222)), (140)GGLG(143) and (239)YF(240), indicating that it should be a new member of the Prx4 family. The deduced CcPrx4 protein had a calculated molecular mass of 27.2 kDa and an estimated isoelectric point of 6.3. Quantitative real-time PCR analysis showed that CcPrx4 mRNA could be detected in all the jellyfish tissues analyzed. CcPrx4 protein was cloned into the expression vector, pET-24a, and expressed in Escherichia coli Rosetta (DE3) pLysS. Recombinant CcPrx4 protein was purified by HisTrap High Performance chelating column chromatography and analyzed for its biological function. The results showed that the purified recombinant CcPrx4 protein manifested the ability to reduce hydrogen peroxide and protect supercoiled DNA from oxidative damage, suggesting that CcPrx4 protein may play an important role in protecting jellyfish from oxidative damage.